The comparative analitical (energy method) and numerical study for the circular plates with ribs. (August 2016) - Popa, C; Marin, C; Negrea, A; Tomescu, G
Abstract: The article analyzes the deformations that are created in a circular plate with radial ribs located on one side, under a concentrated force located at it's center, F = 77000N. To this purpose the deflection obtained by analytically calculating is determined and compares with the displacement obtained by finite element method. To obtain the vertical displacements of a ribbed plate, the results of a similar plane plate, whose vertical displacements were determined, were used and displacements and tensions parameter value, as determined by the analytical method, were introduced.